2015
DOI: 10.1016/j.seppur.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid extraction of lipase produced by psychrotrophic yeast Leucosporidium scottii L117 using aqueous two-phase systems

Abstract: a b s t r a c tAqueous two-phase systems (ATPS) have been used in biomolecules separation and as an efficient alternative to traditional purification systems for lipases extraction. Here, we investigated the partitioning and recovery of lipase derived from Leucosporidium scottii L117 using ATPS and aqueous two-phase micellar systems (ATPMS). Thus, we evaluated three ATPS: (i) polyethylene glycol (PEG)/phosphate salts and (ii) PEG/polyacrylic acid (NaPA) in different molecular weights (1500, 4000 and 8000 g/mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Most of the filamentous fungi and yeast that occurs in Antarctica are cosmopolitan, some were transported to Antarctica by migratory animals, while others called indigenous, are well adapted to the Antarctic environment, and are able to grow and reproduce even at low temperatures (Ruisi et al, ). Survival strategies that have been observed in cold‐adapted yeasts recovered from Antarctic environment, including production of antifreeze proteins (Hashim et al ., ), cold shock and heat shock adaptation (Boo et al ., ), pigment with photoprotective activity (Vaz et al ., ), and cold‐active enzymes (Carrasco et al ., ; Duarte et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Most of the filamentous fungi and yeast that occurs in Antarctica are cosmopolitan, some were transported to Antarctica by migratory animals, while others called indigenous, are well adapted to the Antarctic environment, and are able to grow and reproduce even at low temperatures (Ruisi et al, ). Survival strategies that have been observed in cold‐adapted yeasts recovered from Antarctic environment, including production of antifreeze proteins (Hashim et al ., ), cold shock and heat shock adaptation (Boo et al ., ), pigment with photoprotective activity (Vaz et al ., ), and cold‐active enzymes (Carrasco et al ., ; Duarte et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…; Duarte et al . ) and for bioremediation purposes (Buzzini et al . ), they could present potential for the production of specific metabolites, such as biosurfactants.…”
Section: Introductionmentioning
confidence: 99%
“…According to Buzzini et al (2012), 70 species of yeasts isolated from Antarctica were identified, 13 being ascomycetes and 57 basidiomycetes. Besides their exploitation for the production of coldactive enzymes (Buzzini et al 2012;Duarte et al 2015) and for bioremediation purposes (Buzzini et al 2012), they could present potential for the production of specific metabolites, such as biosurfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efficient methods for recuperation and purification of fermentation products such as enzymes and biologically active proteins are in demand. These systems are composed of two matters soluble in water that are immiscible beyond critical concentration [8][9][10][11][12]. These systems are composed of two matters soluble in water that are immiscible beyond critical concentration [8][9][10][11][12].…”
mentioning
confidence: 99%
“…An alternative method for separation of biomolecules based on aqueous two -phase systems (ATPSs) was proposed by Albertsson, 1985 [7]. These systems are composed of two matters soluble in water that are immiscible beyond critical concentration [8][9][10][11][12]. Varieties of water soluble maters are used for obtaining ATPS.…”
mentioning
confidence: 99%